2019
DOI: 10.1093/isq/sqz040
|View full text |Cite
|
Sign up to set email alerts
|

Drones, Surveillance, and Violence: Theory and Evidence from a US Drone Program

Abstract: We investigate the impact of the US drone program in Pakistan on insurgent violence. Using details about US-Pakistan counterterrorism cooperation and geocoded violence data, we show that the program was associated with monthly reductions of around nine to thirteen insurgent attacks and fifty-one to eighty-six casualties in the area affected by the program. This change was sizable, as in the year before the program, the affected area experienced around twenty-one attacks and one hundred casualties per month. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…A special program using UAs was set up to identify and neutralize rebels in Pakistan. Intelligence analysts, using data from long-term air surveillance and interception of communications, identified the insurgents, which made it quick to target them (Mir, Moore, 2019;Restrepo, 2019).…”
Section: Uas Historical Experiencementioning
confidence: 99%
“…A special program using UAs was set up to identify and neutralize rebels in Pakistan. Intelligence analysts, using data from long-term air surveillance and interception of communications, identified the insurgents, which made it quick to target them (Mir, Moore, 2019;Restrepo, 2019).…”
Section: Uas Historical Experiencementioning
confidence: 99%
“…Where crime is concerned, Do, Ma, and Ruiz (2016) found that, although the deployment of international naval assets off the coast of Somalia did reduce pirate activity, a bigger factor was the presence of privately contracted armed security personnel on board the largest vessels. Studying the impact of US drone strikes in Pakistan, Mir and Moore (2018) found a significant reduction in insurgent violence attributable both to the loss of insurgent personnel and to the deterrent effects of perceived higher risk. Crucially, they found no evidence that the drone strikes resulted in greater support or recruitment by the Pakistan Taliban, which suggests that, in that context, the increased-grievances channel was not very strong.…”
Section: Foreign Military Interventionsmentioning
confidence: 99%
“…The New America Foundation (NAF) has collected data on these strikes from major international, regional, and Western media outlets, tracking the date, location, and estimated casualties of each strike. Their tallies have been used extensively in public discussions about the program's efficacy, as well as academic studies like Johnston and Sarbahi (), Jaegar and Siddique (), and Mir and Moore ().…”
Section: Pakistani Data On Violence and Migrationmentioning
confidence: 99%